PubCrawler: keeping up comfortably with PubMed and GenBank - HOKAMP, KARSTEN; WOLFE, KENNETH (Oxford University Press, 2004)
The free PubCrawler web service (http://www.pubcrawler.ie) has been operating for five years and so far has brought literature and sequence updates to over 22 000 users. It provides information on a personalized web page whenever new articles appear in PubMed or when new sequences are found in GenBank that are specific to customized queries. The server also acts as an automatic alerting system by sending out short notifications or emails with the latest updates as soon as they become available. A new output format and more flexibility for the email formatting help PubCrawler cope with increasing challenges arising from browser incompatibilities and mail filters, therefore making it suitable for a wide range of users.
PUBLISHED
Keywords: Information science (social aspects); Bioinformatics; PubCrawler